Lectotypification of the name Ximenesia encelioides, basionym of Verbesina encelioides (Asteraceae: Heliantheae: Verbesininae) - Juan, Ana; Hind, D.j. Nicholas; Alonso, Mª Angeles (Phytotaxa, 2015)
During the preparation of the treatment for the genus Verbesina Linnaeus (1753: 901) for the Flora iberica (Castroviejo 1986–2015) and work towards a preliminary checklist of the Compositae of Bolivia (Hind 2011), the typification of Verbesina encelioides (Cavanilles 1793: 60) Gray (1876: 350) was reviewed. It is a species with a native distribution apparently along the Gulf coast plains of Texas and Mexico, where it grows on disturbed soils, field margins, roadsides and cultivated areas. Nowadays, V. encelioides is widely distributed as a pantropic weed, behaves as a naturalised plant especially in temperate regions, as well as sometimes cultivated as a half-hardy annual (Hind 2011).